IDENTIFIKASI MORFOLOGI SERANGGA BERPOTENSI SEBAGAI HAMA DAN TINGKAT KERUSAKAN PADA BIBIT MERANTI MERAH (Shorea leprosula) DI PERSEMAIAN PT. SARI BUMI KUSUMA - Abi, .; Oramahi, H A; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2017)
The development of plantations frequently faces technical obstacles, such as the the threat of insect pests. Therefore, pest control is very essential to support the success of development. The investigation is aimed to identify and toget the types of insects that have potential as pests and the level of damage to red timber seed (Shorea Lepsrosula Mig). The study was conducted for 3 months, starting from August to October in the seedbed of PT. Sari Bumi Kusuma, West Kalimantan. The research was conducted through survey on bedside observation. The determination of the beds was employed by purposive sampling i.e the first bed was +6 months old, the second bed was +11 months old, the third bed was +4 months and the fourth bed was +10 months old. The total number of plants observed was 1957 plants. The identification resulted in types of insect pests; 2 orders consisting of 5 families and 5 types of pest insects namely Gryllus mitratus (Cricket), Valanga nigricornis (Grasshoper), Lymantria marginalis (Caterpillar), Spodoptera litura (Taro caterpillar), Pteroma plagiophlps (Bagworm). The symptoms of pest-attacked plants are hollowed leaves, bite marks ranging from the leaf edge to the leaf bone and there is a truncated stem part of the plant. The percentage of plants affected by pest attacks ranged between 10.19% - 56.15% with the average percentage of 23.93% for crop damage categorized as light. The average damage rate ranged from 4.44% to 27.12%. The average rate of crop damage was 10.95% categorized as light damage. Although the level of damage is considered mild but controlling and handling efforts need to be performed in the form of pest eradication that is both mechanically and chemically conducted.Keywords: Morphology Identification, Pest insect, Seeding, Shorea leprosula